Many rotor unmanned aerial vehicle driving system that can portablely change - CHEN JIANWEI; BAI CHAOSHUN; CHEN LIN (2017)
The utility model provides a many rotor unmanned aerial vehicle driving system that can portablely change, relates to the unmanned aerial vehicle field, includes the spiral arm of being connected with the flying machine organism, the spiral arm end is equipped with the motor cabinet, be equipped with two subtend joint holes on the motor cabinet, the motor is installed to the motor cabinet, the motor is connected with an actuating lever that is equipped with thick liquid leaf subassembly, it transfers the mounting groove still to be equipped with an electricity on the spiral arm, it transfers to install the electricity in the electricity accent mounting groove, the electricity transfer with the motor between adopt the banana head to be connected, the utility model discloses whole structure alone, motor, electricity are transferred, and the screw can be dismantled alone and install for the three is quick replacement each other. 种可便携更换的多旋翼无人机动力系统，涉及无人机领域，包括与飞行机机体连接的旋臂，所述旋臂末端设有电机座，所述电机座上设有两个对向卡接孔，所述电机座安装有电机，所述电机与